PERBEDAAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE QUIZ TEAM DAN STUDENT TEAM ACHIEVEMENT DIVISON (STAD) PADA MATA PELAJARAN AL-QUR’AN HADITS - Luthfia Atsira; Afnibar Afnibar; Ilpi Zukdi; Rehani Rehani; Rivdya Eliza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study uses a quantitative method with a quasi-experimental type. The sample was selected using the Cluster Random Sampling technique, with class XI F1 as the Quiz Team class and XI F3 as the STAD class. Data collection used a multiple-choice test of 24 items and documentation. The results showed an average increase in both learning models, where Quiz Team increased by 61.14% and STAD by 61.67% between pre-test and post-test. Hypothesis testing on Quiz Team showed a sig value (2-tailed) of 0.000 <0.05, which means Ha is accepted, namely there is a difference in student learning outcomes before and after using the Quiz Team model. In the STAD model, the hypothesis test showed t count (18.867)> t table (2.037) with a sig value of 0.000 <0.05, which means Ha is accepted, namely there is a difference in learning outcomes before and after implementing the STAD model. However, when the two models were compared using an independent sample t-test, a sig value (2-tailed) of 0.36 > 0.05 was obtained, which indicated that there was no significant difference between the learning outcomes of students using the Quiz Team and STAD models.